2010
DOI: 10.1088/0004-637x/719/1/685
|View full text |Cite
|
Sign up to set email alerts
|

NEW RESULTS FROM THE MAGELLAN IMACS SPECTROSCOPIC Lyα SURVEY: NICMOS OBSERVATIONS OF Lyα EMITTERS ATz= 5.7

Abstract: We present NICMOS J 110 (rest-frame 1200-2100 Å) observations of the three z = 5.7 Lyα emitters discovered in the blind multislit spectroscopic survey by Martin et al. These images confirm the presence of the two sources that were previously only seen in spectroscopic observations. The third source, which is undetected in our J 110 observations, has been detected in narrowband imaging of the Cosmic Origins Survey, so our nondetection implies a rest-frame equivalent width >146 Å (3σ ). The two J 110 -detected s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Nine of the ten galaxies in our sample have Lyα profiles that show both blue and red peaks, and unlike other low redshift samples, their Lyα luminosity and W Lyα reach the range probed by high redshift Lyα surveys (e.g. Ouchi et al 2010;Henry et al 2010Henry et al , 2012.…”
Section: Summary and Discussionmentioning
confidence: 67%
“…Nine of the ten galaxies in our sample have Lyα profiles that show both blue and red peaks, and unlike other low redshift samples, their Lyα luminosity and W Lyα reach the range probed by high redshift Lyα surveys (e.g. Ouchi et al 2010;Henry et al 2010Henry et al , 2012.…”
Section: Summary and Discussionmentioning
confidence: 67%
“…Consequently, a faint LAE could be the result of a low equivalent width emission from a UVbright galaxy, or conversely, high equivalent width emission from an extremely faint galaxy. No obvious trends exist between Lyα luminosity and equivalent width (see Henry et al 2010), although followup of UV-continuum selected i−dropouts shows that fainter continuum is correlated with stronger and more common Lyα emission (Stark et al 2010(Stark et al , 2011. Ultimately, since Lyα equivalent width exhibits such a wide range of values, a statistical comparison with the ensemble of i− dropout galaxies is most relevant.…”
Section: Comparison To Faint Lyα Lfs At Lower Redshiftmentioning
confidence: 99%
“…The sizes of LAEs, on the other hand, require a more careful consideration. Continuum observations show that the majority of LBGs, including those with Lyα emission, have compact sizes at z ∼ 6 (Bouwens et al 2004;Ferguson et al 2004;Henry et al 2010;Malhotra et al 2011;Gronwall et al 2011). Additionally, Hubble Space Telescope imaging of Lyα emission from redshift 3-4 LAEs supports the scenario where Lyα emission is similarly compact (Bond et al 2010;Finkelstein et al 2011).…”
Section: Blind Spectroscopic Datamentioning
confidence: 99%
“…For faint continua, determining the EW is associated with considerable error, and most of pro-claimed high-EWs have huge error bars. For instance, Henry et al (2010) found six sources with W em > 240 Å, but caution that the uncertainties in such high EWs typically exceed 100 Å.…”
Section: Measuring Errorsmentioning
confidence: 99%